1999
DOI: 10.1093/fampra/16.5.528
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of symptoms in Japanese and American depressed primary care patients

Abstract: This study clearly indicates the prominence and importance of physical symptoms in the presentation of depression in Japanese primary care patients. Their physicians must be alerted to the possibility of depression, especially when patient complaints include abdominal, neck or head pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 22 publications
4
45
1
Order By: Relevance
“…31 Interestingly, the specific types of somatic symptoms reported by patients differ between cultures, reflecting cultural patterns of symptom significance-for example, abdominal distress, headaches, and neckaches are reported more frequently by patients with depression from Japan than those from the United States. 33 The high prevalence of somatic symptoms in depression poses the question, "Can somatic symptoms be considered to be clinical predictors of underlying depression in primary care?" It is known that patients with somatic symptoms have a greater risk of developing depression.…”
Section: Somatic Symptoms Are Prevalent In Depression In Primary Carementioning
confidence: 99%
“…31 Interestingly, the specific types of somatic symptoms reported by patients differ between cultures, reflecting cultural patterns of symptom significance-for example, abdominal distress, headaches, and neckaches are reported more frequently by patients with depression from Japan than those from the United States. 33 The high prevalence of somatic symptoms in depression poses the question, "Can somatic symptoms be considered to be clinical predictors of underlying depression in primary care?" It is known that patients with somatic symptoms have a greater risk of developing depression.…”
Section: Somatic Symptoms Are Prevalent In Depression In Primary Carementioning
confidence: 99%
“…Consistent with previous research (Ryder et al, 2008;Waza et al, 1999), Study 1 showed that Chinese emphasized somatic symptoms relative to Westerners in the communication of depression symptoms. We also found evidence of greater somatization to the extent that Chinese participants endorsed the normative expectations of collectivism.…”
Section: Discussionsupporting
confidence: 84%
“…Depression is a global problem associated with multiple social and health issues (1). Medical treatment of depression is mostly unsatisfactory, as exemplified by a recent re-analysis demonstrating the ineffectiveness of a highly promoted class of drugs used for treating depression (2).…”
mentioning
confidence: 99%